Method for treating solid waste, solidified matrix and applications
Patent Information
- Application Number
- CN202611137686.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-27
AI Technical Summary
[0002]燃煤发电行业每年都会产生海量粉煤灰与脱硫石膏,这两类电厂固体废弃物堆存量巨大,长期堆放不仅占用土地资源,还易产生扬尘污染、雨水淋溶渗出有害离子等环境问题
[0039]本申请的固体废弃物的处理方法中,粉煤灰能够提供活性硅铝组分;脱硫石膏能够提供硫酸根离子和钙组分,诱导钙矾石、C-S-H凝胶(水化硅酸钙凝胶)的生成;萤石尾矿能够提供氟化钙组分,在钙基固化剂的作用下填充孔隙,协同提升固化基体的致密性。同时,固体废弃物的总质量份数占比较高,使得固体废弃物能够被充分消耗利用,减少固体废弃物堆存而带来的环境污染影响。水玻璃与氢氧化钠复配作为复合激发剂,能够提供充足的碱激发能力并破坏粉煤灰外壳,使之内部硅铝组分得以充分释放。通过分步骤对各原料进行混合,能够逐级打散原料、使钙基固化剂与复合激发剂均匀包覆固体废弃物,减少制备原料的局部富集;同时,分步骤混合各原料能够减少粉煤灰表面形成水化钝化膜,充分释放硅铝活性组分,提升C-S-H凝胶、钙矾石生成量、同时保证钙离子与氟离子均匀接触,稳定生成CaF2微晶,从而提升固化基体的力学强度、氟离子和重金属离子的固化稳定性、减少超声活化能耗。分步骤养护处理能够大幅降低供热耗能;同时,第一养护处理能够温和启动初期水化反应,释放坯体热应力,防止成型处理后的坯体开裂破损;第二养护处理能够使得水化反应平稳持续进行,均匀生成C-S-H凝胶、钙矾石和CaF2微晶,实现氟离子与重金属离子的均匀固化;第三养护处理能够使水化产物持续熟化填充微孔隙,进一步提升基体的致密性与环保稳定性。上述各原料和工艺步骤协同作用,从而使固化基体具有优良的力学性能和环保性能,具有广泛的应用前景。
Smart Images

Figure CN122977774A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of solid waste treatment technology, and in particular to solid waste treatment methods, solidified substrates and their applications. Background Technology
[0002] The coal-fired power generation industry generates massive amounts of fly ash and desulfurization gypsum annually. The stockpiles of these two types of solid waste from power plants are enormous, and long-term storage not only occupies land resources but also easily causes environmental problems such as dust pollution and the leaching of harmful ions by rainwater. The fluorite tailings generated by the fluorite beneficiation industry contain residual calcium fluoride, soluble fluoride salts, and heavy metal components such as lead and cadmium, classifying them as high-risk industrial solid waste. Direct storage could pose serious risks of groundwater and soil pollution.
[0003] Traditional methods for treating solid wastes such as fly ash, desulfurized gypsum, and fluorite tailings suffer from significant technical bottlenecks, including low utilization rates, high energy consumption, and poor environmental stability. Therefore, further improvements are needed to the treatment methods for these solid wastes. Summary of the Invention
[0004] Based on this, one or more embodiments of this application provide a method for treating solid waste with high compressive strength, low fluoride ion leaching, high heavy metal ion curing rate, and high solid waste utilization rate, as well as a cured substrate and its application.
[0005] According to a first aspect of the embodiments of this application, a method for treating solid waste is provided, comprising the following steps:
[0006] Provide solid waste, including fly ash, fluorite tailings and desulfurized gypsum;
[0007] By mass fractions, 45-55 parts fly ash, 25-35 parts fluorite tailings and 10-20 parts desulfurized gypsum are first mixed to obtain a first mixture;
[0008] The first mixture is mixed with 4-8 parts of calcium-based curing agent and 1-3 parts of composite activator to obtain the second mixture; the composite activator includes water glass and sodium hydroxide.
[0009] The second mixture is mixed with 22-28 parts of water to obtain the third mixture;
[0010] The third mixture was subjected to ultrasonic activation, molding, and curing treatments in sequence to obtain a solidified matrix.
[0011] The maintenance treatment includes a first maintenance treatment, a second maintenance treatment, and a third maintenance treatment performed sequentially. The temperature for the first maintenance treatment is 40℃~50℃, the temperature for the second maintenance treatment is 65℃~75℃, and the temperature for the third maintenance treatment is 20℃~30℃.
[0012] In one embodiment, the solid waste treatment method satisfies at least one of the following characteristics:
[0013] (1) The mass ratio of particles with a diameter >75μm in fly ash is ≤8%;
[0014] (2) The moisture content of fly ash is ≤3%;
[0015] (3) The mass ratio of particles with a diameter > 75 μm in fluorite tailings is ≤ 4%;
[0016] (4) The moisture content of fluorite tailings is ≤4%;
[0017] (5) The particle size of desulfurized gypsum is ≤5mm;
[0018] (6) The moisture content of desulfurized gypsum is 10%~15%.
[0019] In one embodiment, the solid waste treatment method satisfies at least one of the following characteristics:
[0020] (1) Calcium-based curing agents include one or more of quicklime and carbide slag;
[0021] (2) In calcium-based curing agents, the mass content of effective CaO is ≥65%.
[0022] In one embodiment, the solid waste treatment method satisfies at least one of the following characteristics:
[0023] (1) The mass ratio of water glass to sodium hydroxide is (2.5~3.5):1;
[0024] (2) The modulus of water glass is 2~5;
[0025] (3) Water glass includes one or more of sodium water glass, potassium water glass and lithium water glass.
[0026] In one embodiment, the ultrasonic activation treatment has a frequency of 20kHz to 30kHz, a power of 300W to 400W, and a duration of 20min to 30min.
[0027] In one embodiment, the molding process is compression molding, the molding pressure is 18MPa~22MPa, and the molding time is 0.5min~5min.
[0028] In one embodiment, the solid waste treatment method satisfies at least one of the following characteristics:
[0029] (1) The first maintenance treatment should last for 10 to 14 hours;
[0030] (2) The second curing treatment lasts for 20 to 28 hours;
[0031] (3) The third maintenance treatment takes 6 to 8 days.
[0032] In one embodiment, the solid waste treatment method satisfies at least one of the following characteristics:
[0033] (1) The first mixing is a stirring mixing, the first mixing time is 2 min to 4 min, and the first mixing speed is 300 r / min to 500 r / min;
[0034] (2) The second mixing is a stirring mixing, the second mixing time is 1 min to 3 min, and the second mixing speed is 400 r / min to 600 r / min;
[0035] (3) The third mixing is stirring and mixing. The time for the third mixing is 4 min to 6 min, and the speed of the third mixing is 200 r / min to 400 r / min.
[0036] According to a second aspect of the embodiments of this application, a curable substrate is provided, which is prepared by the above-described solid waste treatment method.
[0037] According to a third aspect of the embodiments of this application, an application of the above-mentioned cured substrate is provided, wherein the cured substrate is used for filling mines, preparing roadbed substrates, preparing building blocks, and remediating heavy metal contaminated sites in one or more of the following ways.
[0038] Compared with traditional technologies, this application has the following advantages:
[0039] In the solid waste treatment method of this application, fly ash provides active silica-alumina components; desulfurized gypsum provides sulfate ions and calcium components, inducing the formation of ettringite and CSH gel (hydrated calcium silicate gel); fluorite tailings provide calcium fluoride components, which, under the action of calcium-based solidifying agents, fill pores and synergistically improve the density of the solidified matrix. Simultaneously, the high proportion of total mass of solid waste ensures its full utilization, reducing the environmental pollution impact of solid waste stockpiling. The combination of water glass and sodium hydroxide as a composite activator provides sufficient alkali activation capacity and breaks down the outer shell of fly ash, allowing the internal silica-alumina components to be fully released. By mixing the raw materials in stages, the raw materials can be dispersed step by step, allowing the calcium-based curing agent and composite activator to uniformly coat the solid waste, reducing local enrichment of the raw materials. Simultaneously, the staged mixing of raw materials reduces the formation of a hydration passivation film on the fly ash surface, fully releases the silicon-aluminum active components, increases the generation of CSH gel and ettringite, and ensures uniform contact between calcium and fluoride ions, stably generating CaF2 microcrystals. This improves the mechanical strength of the cured matrix, the curing stability of fluoride and heavy metal ions, and reduces the energy consumption of ultrasonic activation. The staged curing treatment significantly reduces heating energy consumption. The first curing treatment gently initiates the initial hydration reaction, releasing thermal stress in the green body and preventing cracking and breakage after molding. The second curing treatment ensures a stable and continuous hydration reaction, uniformly generating CSH gel, ettringite, and CaF2 microcrystals, achieving uniform curing of fluoride and heavy metal ions. The third curing treatment allows the hydration products to continuously mature and fill micropores, further improving the density and environmental stability of the matrix. The synergistic effect of the above-mentioned raw materials and process steps results in a cured matrix with excellent mechanical and environmental properties, and thus has broad application prospects. Attached Figure Description
[0040] To more clearly illustrate the technical solutions of the specific embodiments of this application, the drawings used in the description of the specific embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings.
[0041] Figure 1 This is a schematic diagram of the microstructure of the mixture in one embodiment of this application;
[0042] Figure 2 This is a schematic diagram of the microstructure of the cured substrate in one embodiment of this application. Detailed Implementation
[0043] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, a detailed description of specific embodiments of this application is provided. Many specific details are set forth in the following description to provide a thorough understanding of this application. However, this application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of this application. Therefore, this application is not limited to the specific embodiments disclosed below.
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. Unless otherwise specifically stated, all raw materials, reagents, instruments, and equipment used in this application are commercially available or can be prepared by existing methods.
[0045] In this application, the terms "multiple", "various", "multiple times", "multi-dimensional", etc., unless otherwise specified, refer to a quantity greater than or equal to 2. For example, "one or more" means one or more than or equal to two.
[0046] The terms “combinations of,” “any combination of,” and “any combination of” used in this article include all suitable combinations of any two or more of the listed items.
[0047] In this document, the term "suitable" as used in phrases such as "suitable combination," "suitable method," and "any suitable method" refers to the ability to implement the technical solution of this application, solve the technical problem of this application, and achieve the expected technical effect of this application.
[0048] In this application, the terms "first aspect," "second aspect," "third aspect," "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," "fourth," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.
[0049] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0050] In this application, numerical intervals (i.e., numerical ranges) are involved. Unless otherwise specified, the selected numerical distributions within the aforementioned numerical intervals are considered continuous and include the two endpoints (i.e., the minimum and maximum values) of the numerical range, as well as every value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints. In this document, this is equivalent to directly listing every integer. For example, if t is an integer selected from 1 to 10, it means that t is any integer selected from the group of integers consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10. Furthermore, when multiple ranges are provided to describe features or characteristics, these ranges can be merged. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges to which they are included.
[0051] Unless otherwise specified, the temperature parameters in this application are permitted to be either constant-temperature treatment or variations within a certain temperature range. It should be understood that the constant-temperature treatment allows temperature fluctuations within the precision range of the instrument control, such as ±5℃, ±4℃, ±3℃, ±2℃, or ±1℃.
[0052] In this application, "room temperature" or "normal temperature" generally refers to 4℃~35℃, for example, 20℃±5℃. In some embodiments of this application, "room temperature" or "normal temperature" refers to 10℃~30℃. In some embodiments of this application, "room temperature" or "normal temperature" refers to 20℃~30℃.
[0053] In this application, %(w / w) and wt% both represent weight percentage, %(v / v) refers to volume percentage, and %(w / v) refers to mass-volume percentage.
[0054] The mass or weight of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship of mass or weight between the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass or weight mentioned in the embodiments of this application can be units known in the chemical industry, such as μg, mg, g, and kg.
[0055] Some embodiments of this application provide a method for treating solid waste, including the following steps:
[0056] Provide solid waste, including fly ash, fluorite tailings and desulfurized gypsum;
[0057] By mass fractions, 45-55 parts fly ash, 25-35 parts fluorite tailings and 10-20 parts desulfurized gypsum are first mixed to obtain a first mixture;
[0058] The first mixture is mixed with 4-8 parts of calcium-based curing agent and 1-3 parts of composite activator to obtain the second mixture; the composite activator includes water glass and sodium hydroxide.
[0059] The second mixture is mixed with 22-28 parts of water to obtain the third mixture;
[0060] The third mixture was subjected to ultrasonic activation, molding, and curing treatments in sequence to obtain a solidified matrix.
[0061] The maintenance treatment includes a first maintenance treatment, a second maintenance treatment, and a third maintenance treatment performed sequentially. The temperature for the first maintenance treatment is 40℃~50℃, the temperature for the second maintenance treatment is 65℃~75℃, and the temperature for the third maintenance treatment is 20℃~30℃.
[0062] In the aforementioned solid waste treatment methods, fly ash provides active silica-alumina components, desulfurized gypsum provides sulfate ions and calcium components, inducing the formation of ettringite and CSH gels, and fluorite tailings provide calcium fluoride components, which, under the action of calcium-based solidifying agents, fill pores and synergistically improve the mechanical properties of the solidified matrix. Simultaneously, the high proportion of total solid waste by mass ensures its full utilization and reduces the environmental pollution impact of solid waste stockpiling.
[0063] The combination of water glass and sodium hydroxide, acting as a composite activator, provides sufficient alkaline activation and breaks down the outer shell of fly ash, allowing the internal silica and aluminum components to be fully released. Specifically, water glass provides silicon-oxygen tetrahedra, which rapidly generate CSH gel with the active aluminum components in fly ash; sodium hydroxide, being highly alkaline, breaks down the glassy outer shell of fly ash, releasing its internal active silica and aluminum. The synergistic effect of these two compounds effectively increases the total amount of hydration products and provides a stable alkaline environment for CaF2 precipitation, inhibiting fluoride ion dissolution. It is understood that fluoride ions dissolved from fluorite tailings can react with calcium ions dissociated from calcium-based solidifiers to form thermodynamically stable CaF2 crystals; the active silica and aluminum components released during fly ash activation can hydrate with desulfurized gypsum to form a network gel structure. Through chemical adsorption, physical encapsulation, and lattice solidification, heavy metal ions are imprisoned within the gel network, blocking ion dissolution channels and achieving long-term, harmless solidification.
[0064] By mixing the raw materials in stages, the primary agglomerates of the raw materials can be gradually broken down, and the calcium-based curing agent and composite activator can uniformly coat the solid waste, reducing local enrichment of the raw materials. At the same time, the staged mixing of raw materials can reduce the formation of a hydration passivation film on the surface of fly ash, fully release the active components of silicon and aluminum, increase the amount of CSH gel and ettringite generated, and ensure uniform contact between calcium ions and fluoride ions, stably generating CaF2 microcrystals. This improves the mechanical strength of the solidified matrix, the curing stability of fluoride ions and heavy metal ions, and reduces the energy consumption of ultrasonic activation. In contrast, the traditional one-step mixing method may cause agglomeration of fluorite tailings and desulfurized gypsum, uneven distribution of curing agent and activator, instantaneous formation of a passivation film when fly ash encounters water and alkali, and difficulty in releasing internal activity; insufficient local calcium source can also lead to incomplete curing of fluoride ions.
[0065] First, the step-by-step curing process of this application can significantly reduce the heat energy consumption of the aforementioned treatment methods. Simultaneously, the first curing process gently initiates the initial hydration reaction, releasing the thermal stress of the formed green body and preventing cracking and damage. The second curing process ensures a stable and continuous hydration reaction, uniformly generating CSH gel, ettringite, and CaF2 microcrystals, achieving uniform solidification by reducing heavy metal ions with fluoride ions. The third curing process allows the hydration products to continuously mature and fill micropores, further enhancing the density and environmental stability of the matrix. In traditional one-step curing, direct contact with high temperatures causes rapid evaporation of moisture and the generation of numerous microcracks. The concentrated burst of the hydration reaction also leads to uneven distribution of gel products, excessively rapid local crystal growth, and an increase in internal interconnected pores. Furthermore, without the third curing process, harmful ions may not be effectively sealed off over a long period.
[0066] As an example, the mass fraction of fly ash can be 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, or 55 parts, or any value within the range formed by any two of the above points.
[0067] Furthermore, the mass fraction of fly ash is 48 to 52 parts; even further, the mass fraction of fly ash is 50 parts.
[0068] As an example, the mass fraction of fluorite tailings can be 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, or 35 parts, or any value within the range formed by any two of the above points.
[0069] Furthermore, the mass fraction of fluorite tailings is 28-32 parts; even further, the mass fraction of fluorite tailings is 30 parts.
[0070] As an example, the mass fraction of desulfurized gypsum can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 parts, or any value within the range formed by any two of the above points.
[0071] Furthermore, the mass fraction of desulfurized gypsum is 12-18 parts; even further, the mass fraction of desulfurized gypsum is 15 parts.
[0072] As an example, the mass fraction of the calcium-based curing agent can be 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, or any value within the range formed by any two of the above points.
[0073] Furthermore, the calcium-based curing agent comprises 5 to 7 parts by mass; even further, the calcium-based curing agent comprises 6 parts by mass.
[0074] As an example, the mass fraction of the composite activator can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, or any value within the range formed by any two of the above point values.
[0075] Furthermore, the mass fraction of the composite activator is 1.5 to 2.5 parts; even further, the mass fraction of the composite activator is 2 parts.
[0076] As an example, the mass fraction of water can be 22, 23, 24, 25, 26, 27, or 28 parts, or any value within the range formed by any two of the above points.
[0077] In some of these embodiments, the water is mixing water.
[0078] It is understandable that controlling the mass fraction of each raw material within the above range can enable the prepared solid substrate to have excellent compressive strength, curing effect of fluoride ions and heavy metal ions, and solid waste consumption efficiency.
[0079] As an example, the temperature of the first curing treatment can be 40℃, 41℃, 42℃, 43℃, 44℃, 45℃, 46℃, 47℃, 48℃, 49℃, 50℃, or any value within the range formed by any two of the above points.
[0080] As an example, the temperature for the second curing treatment can be 65℃, 66℃, 67℃, 68℃, 69℃, 70℃, 71℃, 72℃, 73℃, 74℃, 75℃, or any value within the range formed by any two of the above points.
[0081] As an example, the temperature for the third curing treatment can be 20℃, 21℃, 22℃, 23℃, 24℃, 25℃, 26℃, 27℃, 28℃, 29℃, 30℃, or any value within the range formed by any two of the above points.
[0082] Understandably, in the step-by-step curing method of this application, the low-temperature curing of the first oxygen treatment can gently initiate the initial hydration reaction, slowly build the basic gel skeleton, release the thermal stress caused by the temperature difference between the inside and outside of the green body, and reduce microcracks and surface peeling; the second curing treatment can make the hydration reaction proceed steadily and continuously, and uniformly generate CSH gel, ettringite and CaF2 microcrystals; the third curing treatment can make the unreacted active components continue to hydrate, fill the micropores a second time, and make heavy metal ions continuously embed into the crystal lattice, effectively sealing the ion dissolution channels.
[0083] The curing treatment in this application uses a low temperature of no more than 75°C, eliminating the need for calcination and high-temperature sintering of the desulfurized gypsum, thus significantly reducing production energy consumption and carbon emissions.
[0084] In some embodiments, before mixing fly ash, fluorite tailings and desulfurized gypsum, the following steps are included: ball milling, screening and drying the fly ash in sequence.
[0085] In some embodiments, the mass ratio of particles with a diameter >75 μm in the fly ash is ≤8%. In other words, the mass ratio of particles with a diameter ≤75 μm in the fly ash is >92%.
[0086] In some of these embodiments, the moisture content of the fly ash is ≤3%.
[0087] In some embodiments, before mixing fly ash, fluorite tailings and desulfurized gypsum, the following steps are included: sequentially subjecting the fluorite tailings to ball milling, washing, screening and drying.
[0088] It is understandable that washing fluorite tailings with water can effectively remove soluble fluoride salts from them.
[0089] In some embodiments, the mass ratio of particles with a diameter >75 μm in the fluorite tailings is ≤4%. In other words, the mass ratio of particles with a diameter ≤75 μm in the fluorite tailings is >96%.
[0090] In some of these embodiments, the moisture content of the fluorite tailings is ≤4%.
[0091] In some embodiments, before mixing fly ash, fluorite tailings and desulfurized gypsum, the following steps are included: ball milling and sieving the desulfurized gypsum in sequence.
[0092] In some of these embodiments, high-temperature calcination of the desulfurized gypsum is not required.
[0093] In some of these embodiments, the particle size of the desulfurized gypsum is ≤5 mm.
[0094] In some of these embodiments, the desulfurized gypsum has a moisture content of 10% to 15%.
[0095] As an example, the moisture content of desulfurized gypsum can be 10%, 11%, 12%, 13%, 14%, 15%, or any value within the range formed by any two of the above points.
[0096] In some embodiments, the calcium-based curing agent includes one or more of quicklime and carbide slag.
[0097] In some embodiments, the effective CaO content in the calcium-based curing agent is ≥65% by mass.
[0098] It is understandable that "effective CaO" refers to free calcium oxide that can undergo hydration reactions with water and has gelling activity.
[0099] In some embodiments, the mass ratio of water glass to sodium hydroxide is (2.5~3.5):1.
[0100] As an example, the mass ratio of water glass to sodium hydroxide can be 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, or any value within the range of any two of the above ratios.
[0101] It is understandable that the mass ratio of water glass to sodium hydroxide can affect the strength properties and fluoride ion leaching content of the cured substrate. Specifically, if the ratio of water glass to sodium hydroxide is less than 2.5:1, efflorescence may occur due to excessive alkali content, thus affecting the durability of the cured substrate. If the ratio of water glass to sodium hydroxide is greater than 3.5:1, the fly ash may not be fully activated.
[0102] In some embodiments, the modulus of the water glass is 1.2 to 1.5.
[0103] As an example, the modulus of water glass can be 1.2, 1.3, 1.4, 1.5, or any value within the range formed by any two of the above point values.
[0104] It is understandable that "the modulus of water glass" refers to the ratio of the amount of silicon dioxide to the amount of oxides.
[0105] In some embodiments, the water glass includes one or more of sodium water glass, potassium water glass, and lithium water glass.
[0106] Furthermore, the water glass is sodium water glass.
[0107] like Figure 1 As shown, before the mixture was ultrasonically activated, the solid waste particles were in a discrete state; fly ash was a smooth spherical glass, fluorite tailings were irregular angular particles, and desulfurized gypsum was a flaky crystal. Each component was independent of the others, with loose interfaces, huge pores, no cementing products, easy ion dissolution, and poor structural stability.
[0108] In some embodiments, the ultrasonic activation treatment is performed at a frequency of 20kHz to 30kHz, a power of 300W to 400W, and a duration of 20min to 30min.
[0109] As an example, the frequency of ultrasonic activation treatment can be 20kHz, 21kHz, 22kHz, 23kHz, 24kHz, 25kHz, 26kHz, 27kHz, 28kHz, 29kHz, 30kHz, or any value within the range formed by any two of the above points.
[0110] As an example, the power of the ultrasonic activation treatment can be 300W, 310W, 320W, 330W, 340W, 350W, 360W, 370W, 380W, 390W, 400W, or any value within the range formed by any two of the above points.
[0111] As an example, the ultrasonic activation treatment time can be 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, or any value within the range formed by any two of the above points.
[0112] In some embodiments, the forming process is compression molding.
[0113] In some embodiments, the molding process pressure is 18MPa~22MPa, and the molding process time is 0.5min~1.5min.
[0114] As an example, the pressure for the molding process can be 18MPa, 19MPa, 20MPa, 21MPa, 22MPa, or any value within the range formed by any two of the above points.
[0115] As an example, the molding process time can be 0.5 min, 0.6 min, 0.7 min, 0.8 min, 0.9 min, 1 min, 1.1 min, 1.2 min, 1.3 min, 1.4 min, 1.5 min, or any value within the range formed by any two of the above points.
[0116] In some embodiments, the first curing treatment lasts for 10 to 14 hours.
[0117] As an example, the time for the first maintenance treatment can be 10h, 11h, 12h, 13h, 14h, or any value within the range formed by any two of the above points.
[0118] In some embodiments, the second curing treatment lasts for 20 to 28 hours.
[0119] As an example, the time for the second maintenance treatment can be 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, or any value within the range formed by any two of the above point values.
[0120] In some embodiments, the third maintenance treatment lasts for 6 to 8 days. As an example, the third maintenance treatment can last for 6 days, 6.5 days, 7 days, 7.5 days, 8 days, or any value within the range formed by any two of the above points.
[0121] In some embodiments, the first mixing is a stirring mixture.
[0122] In some embodiments, the first mixing time is 2 to 4 minutes. As an example, the first mixing time can be 2 minutes, 2.5 minutes, 3 minutes, 3.5 minutes, 4 minutes, or any value within the range formed by any two of the above points.
[0123] In some embodiments, the rotational speed of the first mixing is 300 r / min to 500 r / min. As an example, the rotational speed of the first mixing can be 300 r / min, 310 r / min, 320 r / min, 330 r / min, 340 r / min, 350 r / min, 360 r / min, 370 r / min, 380 r / min, 390 r / min, 400 r / min, 410 r / min, 420 r / min, 430 r / min, 440 r / min, 450 r / min, 460 r / min, 470 r / min, 480 r / min, 490 r / min, or 500 r / min, or any value within the range formed by any two of the above values. In some embodiments, the second mixing is a stirring mixture.
[0124] In some embodiments, the second mixing time is 1 min to 3 min. As an example, the second mixing time can be 1 min, 1.5 min, 2 min, 2.5 min, 3 min, or any value within the range formed by any two of the above point values.
[0125] In some embodiments, the rotational speed of the second mixing is 400 r / min to 600 r / min. As an example, the rotational speed of the second mixing can be 400 r / min, 410 r / min, 420 r / min, 430 r / min, 440 r / min, 450 r / min, 460 r / min, 470 r / min, 480 r / min, 490 r / min, 500 r / min, 510 r / min, 520 r / min, 530 r / min, 540 r / min, 550 r / min, 560 r / min, 570 r / min, 580 r / min, 590 r / min, 600 r / min, or any value within the range formed by any two of the above points.
[0126] In some embodiments, the third mixing is a stirring mixture.
[0127] In some embodiments, the third mixing time is 4 to 6 minutes. As an example, the third mixing time can be 4 minutes, 4.5 minutes, 5 minutes, 5.5 minutes, 6 minutes, or any value within the range formed by any two of the above point values.
[0128] In some embodiments, the rotational speed of the third mixing is 200 r / min to 400 r / min. As an example, the rotational speed of the third mixing can be 200 r / min, 210 r / min, 220 r / min, 230 r / min, 240 r / min, 250 r / min, 260 r / min, 270 r / min, 280 r / min, 290 r / min, 300 r / min, 310 r / min, 320 r / min, 330 r / min, 340 r / min, 350 r / min, 360 r / min, 370 r / min, 380 r / min, 390 r / min, 400 r / min, or any value within the range formed by any two of the above points.
[0129] It is understandable that controlling the rotation speeds of the first, second, and third mixing processes within the aforementioned ranges can ensure that each material is evenly coated and does not agglomerate.
[0130] like Figure 2As shown, after ultrasonic activation, molding and curing, a large amount of flocculent CSH hydration gel, needle-like ettringite crystals and diffusely distributed CaF2 stable microcrystals are generated. All solid waste particles are tightly wrapped and overlapped by the gel system, the large pores are fully filled, the overall structure is dense and homogeneous, the mechanical properties are greatly improved, and the harmful ions are sealed and solidified at the same time.
[0131] In the above-mentioned solid waste treatment methods, the wastewater after curing treatment and the washing wastewater of fluorite tailings can be recycled after unified collection and sedimentation treatment, and can be used for washing fluorite tailings or as raw material water for preparation; thus, the impact of wastewater discharge on the environment can be reduced and the efficiency of resource utilization can be improved.
[0132] The above-mentioned solid waste treatment methods can efficiently dispose of three types of solid waste: fly ash, fluorite tailings, and desulfurized gypsum, effectively improving the problem of solid waste stockpiling.
[0133] Some embodiments of this application also provide a cured substrate, which is prepared using the above-described solid waste treatment method.
[0134] The cured substrate described in this application has a 28-day compressive strength ≥30MPa, which can meet the requirements of multiple engineering fields such as mine filling, roadbed building materials, and ecological solidification, and has a wide range of applications.
[0135] Some embodiments of this application also provide an application of the above-mentioned cured substrate, which is used for filling mines, preparing roadbed substrates, preparing building blocks, and remediating sites contaminated with heavy metals in one or more of the following applications.
[0136] The present application will be further described below with reference to specific embodiments and comparative examples, but these should not be construed as limiting the scope of protection of the present application. Unless otherwise specified, the raw materials involved in the following specific embodiments are all commercially available, the instruments used are all commercially available, and the processes involved are conventionally selected by those skilled in the art unless otherwise specified.
[0137] Example 1
[0138] (1) Raw material pretreatment: The fly ash was ball-milled to a residue of 7% on a 200-mesh sieve (i.e., the mass ratio of particles with a diameter > 75 μm was 7%), and dried to a moisture content of 2.5%; the fluorite tailings were ball-milled to a residue of 4% on a 200-mesh sieve (i.e., the mass ratio of particles with a diameter > 75 μm was 4%), washed with water to remove soluble fluoride salts, and dried to a moisture content of 3%; the desulfurized gypsum was crushed to a particle size ≤ 5 mm, and the original moisture content was 12%.
[0139] (2) Weigh out 50 parts of fly ash, 30 parts of fluorite tailings, 15 parts of desulfurized gypsum, 6 parts of quicklime, 2 parts of composite activator, and 25 parts of mixing water by mass; wherein the composite activator is water glass with a modulus of 1.3 and sodium hydroxide mixed at a mass ratio of 3:1.
[0140] (3) Dry mix fly ash, fluorite tailings, and desulfurized gypsum at 400 r / min for 3 min; then add calcium-based curing agent and composite activator and dry mix at 500 r / min for 2 min; then add water and wet mix at 300 r / min for 5 min to obtain a mixture. Ultrasonically activate the mixture at 25 kHz and 350 W for 25 min.
[0141] (4) Press the ultrasonically activated mixture under a pressure of 20 MPa and hold the pressure for 1 min to obtain a green blank.
[0142] (5) The above-mentioned green blank is first cured at 45℃ for 12 hours, then cured at 70℃ for 24 hours, and then cured at room temperature for 7 days to obtain a cured substrate.
[0143] Example 2
[0144] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Example 2 include: 45 parts fly ash, 35 parts fluorite tailings, 10 parts desulfurized gypsum, 8 parts calcium carbide slag, 1 part composite activator, and 22 parts mixing water.
[0145] Example 3
[0146] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Example 3 include: 55 parts fly ash, 25 parts fluorite tailings, 20 parts desulfurized gypsum, 4 parts quicklime, 3 parts composite activator, and 22 parts mixing water.
[0147] Example 4
[0148] The process is basically the same as in Example 1, except that the curing temperature is different in step (5). Specifically, the curing steps in Example 4 include: first curing the above green blank at 50°C for 12 hours, then curing it at a constant temperature of 75°C for 24 hours, and then curing it at room temperature for 7 days to obtain a cured substrate.
[0149] Example 5
[0150] It is basically the same as Example 1, except that the ultrasonic activation time in step (4) is different. Specifically, the ultrasonic activation time in Example 5 is 30 min.
[0151] Example 6
[0152] The results are essentially the same as in Example 1, except for the different mass ratio of water glass to sodium hydroxide. Specifically, in Example 6, the mass ratio of water glass to sodium hydroxide is 3.5:1.
[0153] Comparative Example 1
[0154] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 1 include: 40 parts fly ash, 20 parts fluorite tailings, 15 parts desulfurized gypsum, 6 parts quicklime, 2 parts composite activator, and 25 parts mixing water.
[0155] Comparative Example 2
[0156] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 2 include: 50 parts fly ash, 30 parts fluorite tailings, 15 parts desulfurized gypsum, 2 parts composite activator, and 25 parts mixing water.
[0157] Comparative Example 3
[0158] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 3 include: 50 parts fly ash, 30 parts fluorite tailings, 15 parts desulfurized gypsum, 6 parts quicklime, and 25 parts mixing water.
[0159] Comparative Example 4
[0160] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 4 include: 40 parts fly ash, 30 parts fluorite tailings, 15 parts desulfurized gypsum, 6 parts quicklime, 2 parts composite activator, and 25 parts mixing water.
[0161] Comparative Example 5
[0162] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 5 include: 60 parts fly ash, 30 parts fluorite tailings, 15 parts desulfurized gypsum, 6 parts quicklime, 2 parts composite activator, and 25 parts mixing water.
[0163] Comparative Example 6
[0164] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 6 include: 50 parts fly ash, 20 parts fluorite tailings, 15 parts desulfurized gypsum, 6 parts quicklime, 2 parts composite activator, and 25 parts mixing water.
[0165] Comparative Example 7
[0166] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 7 include: 50 parts fly ash, 40 parts fluorite tailings, 15 parts desulfurized gypsum, 6 parts quicklime, 2 parts composite activator, and 25 parts mixing water.
[0167] Comparative Example 8
[0168] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 8 include: 50 parts fly ash, 30 parts fluorite tailings, 5 parts desulfurized gypsum, 6 parts quicklime, 2 parts composite activator, and 25 parts mixing water.
[0169] Comparative Example 9
[0170] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 9 include: 50 parts fly ash, 30 parts fluorite tailings, 25 parts desulfurized gypsum, 6 parts quicklime, 2 parts composite activator, and 25 parts mixing water.
[0171] Comparative Example 10
[0172] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 10 include: 50 parts fly ash, 30 parts fluorite tailings, 15 parts desulfurized gypsum, 2 parts quicklime, 2 parts composite activator, and 25 parts mixing water.
[0173] Comparative Example 11
[0174] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 11 include: 50 parts fly ash, 30 parts fluorite tailings, 15 parts desulfurized gypsum, 10 parts quicklime, 2 parts composite activator, and 25 parts mixing water.
[0175] Comparative Example 12
[0176] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 12 include: 50 parts fly ash, 30 parts fluorite tailings, 15 parts desulfurized gypsum, 6 parts quicklime, 0.5 parts composite activator, and 25 parts mixing water.
[0177] Comparative Example 13
[0178] The results are basically the same as in Example 1, except that the mass fractions of the raw materials are different. Specifically, the raw materials in Comparative Example 13 include: 50 parts fly ash, 30 parts fluorite tailings, 15 parts desulfurized gypsum, 6 parts quicklime, 4 parts composite activator, and 25 parts mixing water.
[0179] Comparative Example 14
[0180] The results are basically the same as in Example 1, except that step (3) is different. Specifically, step (3) in Comparative Example 14 includes: mixing fly ash, fluorite tailings, desulfurized gypsum, calcium-based curing agent, composite activator and water together for 20 min; and then ultrasonically activating at 25 kHz and 350 W for 25 min.
[0181] Comparative Example 15
[0182] It is basically the same as Example 1, except that step (5) is different. Specifically, step (5) in Comparative Example 15 includes: directly subjecting the sample to continuous humid heat oxygenation at 70°C for 46 hours.
[0183] Comparative Example 16
[0184] The results are essentially the same as in Example 1, except for the different composite activator. Specifically, in Comparative Example 16, the composite activator is 2 parts of water glass with a modulus of 1.3.
[0185] In the above embodiments and comparative examples, some raw materials and process parameters are shown in Table 1.
[0186] Table 1. Raw material and process parameters for Examples 1-5 and Comparative Examples 1-16
[0187]
[0188] Performance testing
[0189] According to GB / T 17671-2021 Cement Mortar Strength Test Method (ISO Method), the compressive strength of the cured substrate was tested using a YAW-300 microcomputer-controlled pressure testing machine. According to HJ / T 299-2007 Solid Waste Leaching Toxicity Leaching Method Sulfuric Acid and Nitric Acid Method, the fluoride ion leaching amount was tested using an ion chromatograph (ICS-600). Referring to the leaching method described in HJ / T 299-2007, the lead and cadmium heavy metal curing rate was tested using an atomic absorption spectrophotometer (AA-6300). Curing rate = (Total heavy metals in raw materials - Leached heavy metals) / Total heavy metals in raw materials × 100%. Solid waste utilization rate refers to the ratio of the total mass of fly ash, fluorite tailings, and desulfurized gypsum to the total mass of all solid raw materials. All solid raw materials include fly ash, fluorite tailings, desulfurized gypsum, calcium-based solidifying agent, and composite activator. That is, solid waste utilization rate = (mass of fly ash + mass of fluorite tailings + mass of desulfurized gypsum) / (mass of fly ash + mass of fluorite tailings + mass of desulfurized gypsum + mass of calcium-based solidifying agent + mass of composite activator) × 100%. The performance test results of the above embodiments and comparative examples are shown in Table 2.
[0190] Table 2 Performance test results of Examples 1-5 and Comparative Examples 1-16
[0191]
[0192] The main difference between Examples 1 to 3 lies in the different mass fractions of the raw materials. The cured substrate prepared in Example 1 has higher compressive strength and no heavy metal leaching was detected. It can be seen that using the mass fraction of Example 1 can achieve better technical results.
[0193] The main difference between Example 1 and Example 4 lies in the curing temperature. The hydration rate is accelerated in the treatment method of Example 4, but the cured substrate prepared in Example 1 has fewer internal microcracks and higher compressive strength. It can be seen that the curing temperature of Example 1 can achieve better technical results.
[0194] The main difference between Example 1 and Example 5 lies in the ultrasonic activation time. Compared with Example 1, the ultrasonic activation time of Example 5 can slightly improve the activity of fly ash, but the improvement is limited. In contrast, the ultrasonic activation time of Example 1 can balance low energy consumption and high performance.
[0195] In Comparative Example 1, the total amount of solid waste decreased significantly, and the supply of active silica-alumina and calcium sulfate components in the system was insufficient, resulting in a reduction in the amount of hydration gel generated and a decrease in the density of the matrix. The strength of the prepared cured material was lower than the 30 MPa specified by the engineering standard, and the fluoride ion leaching exceeded the standard, significantly reducing the sealing and curing effect of heavy metals.
[0196] Comparative Example 2 did not contain a calcium-based curing agent, and the system lacked free Ca. 2+ F cannot be dissolved from fluorite tailings - The formation of stable CaF2 microcrystals leads to the leaching and precipitation of large amounts of soluble fluorine, increasing environmental risks. At the same time, the lack of sufficient calcium source to support the CSH gel and ettringite hydration reaction results in extremely low production of gel products, a loose and porous matrix, substandard compressive strength, and the inability to effectively confine heavy metal ions.
[0197] In Comparative Example 3, no composite activator was added, which could not break the dense glassy shell of fly ash, making it difficult to release the internal active silica-alumina components and resulting in a low overall degree of hydration reaction. The formation of hydration gel and ettringite was insufficient, the matrix pores were highly interconnected, the compressive strength was greatly reduced, and fluorine and heavy metal ions were easily migrated and dissolved with water.
[0198] In Comparative Example 4, the mass fraction of fly ash was less than 45 parts, the active silica-alumina component was insufficient, the amount of hydration gel generated was low, resulting in substandard compressive strength and reduced curing effect of fluorine and heavy metals.
[0199] In Comparative Example 5, the mass fraction of fly ash was higher than 55 parts, indicating a relatively insufficient calcium source. This prevented sufficient precipitation of fluoride ions, resulting in excessive fluoride ion leaching.
[0200] In Comparative Example 6, the mass fraction of fluorite tailings was less than 25 parts, resulting in a significant reduction in consumption and a substantial decrease in solid waste utilization.
[0201] In Comparative Example 7, the mass fraction of fluorite tailings was higher than 35 parts, resulting in an excessively high total amount of fluoride ions. The calcium-based curing agent could not completely precipitate the fluoride ions, thus causing the fluoride ion leaching to exceed the standard. At the same time, it increased the porosity of the cured matrix and reduced its compressive strength.
[0202] In Comparative Example 8, the mass fraction of desulfurized gypsum was less than 10 parts, resulting in insufficient supply of sulfate and calcium ions, which led to a low amount of ettringite formation, poor matrix density, numerous ion dissolution channels, and low compressive strength.
[0203] In Comparative Example 9, the mass fraction of desulfurized gypsum was higher than 20 parts. It generated expansion stress in the later stage of treatment, making it difficult for the compressive strength of the cured matrix to meet the standard, and its long-term stability was poor.
[0204] In Comparative Example 10, the mass fraction of calcium-based curing agent was less than 4 parts, resulting in insufficient calcium ion supply in the system and the inability to generate sufficient CaF2. This led to a large amount of fluoride ions dissolving out, incomplete hydration reaction, and a significant increase in the fluoride ion leaching rate.
[0205] In Comparative Example 11, the mass fraction of calcium-based curing agent was higher than 8 parts, resulting in excessive free calcium oxide in the system. This made the finished product prone to expansion and cracking, and the strength of the cured matrix was substandard, leading to a decrease in solid waste utilization.
[0206] In Comparative Example 12, the mass fraction of the composite activator was less than 1 part, indicating insufficient activating components in the system, inadequate activation of the fly ash vitreous, and a low amount of gel product. The compressive strength and heavy metal curing rate of the resulting cured matrix were both low.
[0207] In Comparative Example 13, the mass fraction of the composite activator was higher than 3 parts, resulting in an excess of alkali components in the system. This led to severe alkali efflorescence in the cured matrix, slight excess of fluorine leaching, and decreased long-term durability.
[0208] In Comparative Example 14, a one-step activation method was used instead of the stepwise activation in Example 1, which resulted in the accumulation of raw materials and component segregation; a passivation film was formed on the surface of fly ash, resulting in insufficient release of active ingredients; the calcium ion distribution in the system was uneven, which prevented the complete precipitation of local fluoride ions; and the final solidified matrix had interconnected pores, and its compressive strength and environmental protection indicators did not meet the standards.
[0209] In Comparative Example 15, a one-step constant temperature curing method was used instead of a multi-step curing method. During the process, the thermal stress of the green body was concentrated, resulting in a large number of microcracks. The hydration reaction was instantaneously triggered, which led to the development of pores. Furthermore, the treatment method in Comparative Example 15 lacked a room temperature curing stage, so the micropores could not be filled, and the long-term curing effect of fluoride ions and heavy metal ions was greatly reduced.
[0210] In Comparative Example 16, the absence of sodium hydroxide significantly reduced the alkali activation capacity of the solid waste system, and also resulted in a marked decrease in the compressive strength of the solidified material and an increase in the leaching of fluoride ions.
[0211] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0212] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this application should be determined by the appended claims.
Claims
1. A method for treating solid waste, characterized in that, Includes the following steps: Provide solid waste, including fly ash, fluorite tailings and desulfurized gypsum; By mass fractions, 45-55 parts fly ash, 25-35 parts fluorite tailings and 10-20 parts desulfurized gypsum are first mixed to obtain a first mixture; The first mixture is mixed with 4-8 parts of calcium-based curing agent and 1-3 parts of composite activator to obtain a second mixture; the composite activator includes water glass and sodium hydroxide. The second mixture is mixed with 22-28 parts of water to obtain a third mixture; The third mixture was subjected to ultrasonic activation treatment, molding treatment and curing treatment in sequence to obtain a solidified matrix; The maintenance treatment includes a first maintenance treatment, a second maintenance treatment, and a third maintenance treatment performed sequentially. The temperature of the first maintenance treatment is 40℃~50℃, the temperature of the second maintenance treatment is 65℃~75℃, and the temperature of the third maintenance treatment is 20℃~30℃.
2. The method for treating solid waste according to claim 1, characterized in that, The solid waste treatment method satisfies at least one of the following characteristics: (1) The mass ratio of particles with a particle size > 75 μm in the fly ash is ≤ 8%; (2) The moisture content of the fly ash is ≤3%; (3) The mass ratio of particles with a diameter > 75 μm in the fluorite tailings is ≤ 4%; (4) The moisture content of the fluorite tailings is ≤4%; (5) The particle size of the desulfurized gypsum is ≤5mm; (6) The moisture content of the desulfurized gypsum is 10%~15%.
3. The method for treating solid waste according to claim 1, characterized in that, The solid waste treatment method satisfies at least one of the following characteristics: (1) The calcium-based curing agent includes one or more of quicklime and carbide slag; (2) The effective CaO content in the calcium-based curing agent is ≥65%.
4. The method for treating solid waste according to claim 1, characterized in that, The solid waste treatment method satisfies at least one of the following characteristics: (1) The mass ratio of the water glass to the sodium hydroxide is (2.5~3.5):1; (2) The modulus of the water glass is 1.2~1.5; (3) The water glass includes one or more of sodium water glass, potassium water glass and lithium water glass.
5. The method for treating solid waste according to any one of claims 1 to 4, characterized in that, The ultrasonic activation treatment has a frequency of 20kHz~30kHz, a power of 300W~400W, and a duration of 20min~30min.
6. The method for treating solid waste according to any one of claims 1 to 4, characterized in that, The molding process is compression molding, the molding pressure is 18MPa~22MPa, and the molding time is 0.5min~1.5min.
7. The method for treating solid waste according to any one of claims 1 to 4, characterized in that, The solid waste treatment method satisfies at least one of the following characteristics: (1) The duration of the first maintenance treatment is 10h~14h; (2) The duration of the second maintenance treatment is 20h~28h; (3) The duration of the third maintenance treatment is 6 to 8 days.
8. The method for treating solid waste according to any one of claims 1 to 4, characterized in that, The solid waste treatment method satisfies at least one of the following characteristics: (1) The first mixing is a stirring mixing, the first mixing time is 2 min to 4 min, and the first mixing speed is 300 r / min to 500 r / min; (2) The second mixing is a stirring mixing, the second mixing time is 1 min to 3 min, and the second mixing speed is 400 r / min to 600 r / min; (3) The third mixing is a stirring mixing, the third mixing time is 4 min to 6 min, and the third mixing speed is 200 r / min to 400 r / min.
9. A cured substrate, characterized in that, It is prepared by the solid waste treatment method according to any one of claims 1 to 8.
10. An application of the cured substrate according to claim 9, characterized in that, The cured substrate is used for one or more of the following: filling mines, preparing roadbed substrates, preparing building blocks, and remediating sites contaminated with heavy metals.